Influence of Modern Cableways on the Development of Mountain Tourist Centres - Težak, Sergej; Mavrin, Ivan; Jurić, Ivo (Promet - Traffic&Transportation, 2005)
The paper studies the problem of constructing cablewayswith advanced technology and their influence on the operationand development of cableway companies from several aspects.Modern cableways with detachable grips enable faster ca’iageof passengers. They have the possibility of transporting morepassengers over the same distances. Recently, this trend of introducingmodern cableways has been particularly present inchairlifts which carry skiers. Such chairlifts with detachablegrips allow transport of skiers over greater distances and thereforemust have respective ski slopes covering wider areas whichin turn affects the expansion of the mountain tourist centres.The chairlifts with detachable grips require more knowledgeand personnel to manage and maintain them, as well as moreinvestment capital.